Evaluasi Spesifik Lokasi terhadap Kualitas Udara dan Tanah dalam Mendukung Keberlanjutan Pertanian di Desa Kebontunggul, Kecamatan Gondang, Kabupaten Mojokerto. - Fajar Purwanto Putra; Soesanto Soesanto; Sari Rahayu; Dimas Ganda Permana Putra; Zenita Afifah Fitriyani (Politeknik Negeri Lampung., 2025)
Air quality and soil fertility are critical factors for sustaining agricultural productivity. This study, conducted in Kebontunggul Village from July to September 2025, evaluated ambient air quality and soil fertility at two distinct sites. Results indicated that major air pollutants such as SO₂, NO₂, O₃, and CO remained below permissible limits, suggesting relatively safe conditions, though variations in NH₃, Pb, and TSP highlight potential long-term risks requiring monitoring. Soil analysis revealed contrasting characteristics: Site 1 had low available phosphorus (4.20 mg/kg) but higher organic carbon (3.36%), while Site 2 showed higher phosphorus (7.24 mg/kg) yet lower organic carbon (2.85%). These findings underscore the need for site-specific management strategies, with organic inputs prioritized at Site 2 and phosphorus fertilization emphasized at Site 1 to enhance productivity while maintaining agricultural sustainability.